Gender Inequality and Economic Growth in Nepal: An ECM Approach - Acharya, Bashanti (Journal of Research and Analysis, 2026)
This study explores the impact of gender inequality on economic growth in Nepal by examining the long-run relationship between Gross Domestic Product per capita (GDP per capita) and three key gender-related indicators: female secondary school enrollment, women’s representation in national parliaments, and the female-to-male labor force participation ratio. Using co-integration and error correction modeling on data from 1991 to 2023, the analysis confirms that all variables are integrated of order one, justifying the use of co-integration techniques. The results reveal a statistically significant and positive long-term association between gender inclusion and economic growth, with female labor participation exerting the strongest influence, followed by educational attainment and political representation. The stationarity of residuals and the significant error correction term affirm the existence of a stable equilibrium, while Granger causality tests suggest that economic growth drives female labor participation and highlight short-run inter-linkages between education and political empowerment. With a high explanatory power (R2 = 0.9873), the findings reinforce the theoretical view that gender inequality constrains economic development. This study offers critical empirical evidence and recommends gender-inclusive and socially equitable policies that promote educational access, labor market inclusion, and political representation for women, ultimately contributing to the achievement of the sustainable development goals targets.